Pengembangan Media Kartu Peluang Untuk Menunjang Pembelajaran Matematika - Rizkia Tiara Putri Gumilar; Abdullah Hammuda Ramadhan; Iif Nadiatul Ulumiah; Sri Hastuti Rhomawati (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The importance of using media in the mathematics learning process has become the main focus in increasing the effectiveness and attractiveness of learning. One interesting approach is the development of opportunity card-based learning media. This research aims to develop and release opportunity card media as a mathematics learning aid that can increase students' understanding of concepts and interest in learning. This media development is carried out through the stages of requirements, design analysis, development and evaluation. The research method used is development research using the Kemp model which includes several stages, such as needs analysis, planning, development, implementation and evaluation. Each stage has specific steps that help process developers design and organize learning materials more effectively. The research subjects involved class XII students at SMA Negeri 62 Jakarta. The research results showed that the opportunity card media developed received a positive response from students and teachers. Understanding of mathematical concepts increased significantly, and students' interest in learning also increased. and also provide an interesting learning experience and can increase student involvement in learning.